Heavy ions at the LHC: Selected predictions - Mehtar-Tani, Yacine; Wolschin, Georg (Journal of physics. Conference Series, 2011)
Baryon transport in relativistic heavy-ion collisions is investigated within a gluon saturation model. The theoretical results are compared with Pb + Pb data at SPS, and Au + Au data at RHIC energies. Predictions are made for net-baryon and net-proton rapidity distributions in central Pb + Pb collisions at CERN LHC energies of up to ##IMG## [http://ej.iop.org/images/1742-6596/312/1/012016/jpconf11_312_012016eqn1.gif] TeV both at forward rapidities, and in the central rapidity region where data will soon be available.